Transient Response of Multiple Interface Cracks in Fine-Grained Coating Composite Structures under Impact Loading - Shuaishuai Hu; Junlin Li (Advances in Mathematical Physics)
The mechanical behavior of the fine-grained piezoelectric/substrate structure with multiple interface cracks under the electromechanical impact loading is investigated. Using the Laplace and Fourier integral transforms, the double-coupled singular integral equations and single-valued conditions of the problems are formulated. Both the singular integral equation and single-valued conditions are simplified into an algebraic equation through the Chebyshev point placement method and solved by numerical calculation. Then, the expression of the dynamic energy release rate is given with the help of the dynamic intensity factors of electric displacement and stress obtained. Finally, numerical results of the dynamic energy release rate with material parameters are demonstrated. The results show that the dynamic energy release rate depends on the size of the interface cracks, coating thickness, and the mechanical–electrical loading. Meanwhile, the fine-grained piezoelectric structures exhibit safer structural performance compared to normal one.